Pengaruh Penggunaan Game Edukasi Berbasis Digital Terhadap Pemahaman Konsep Sains - Mukminah; Yolanda Aprilianti; Herjan Haryadi (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This study aims to determine the effect of using digital educational games on the understanding of science concepts among fifth-grade students at SDN 3 Gunungsari. This research uses a quantitative approach with a quasi-experimental design (nonequivalent control group design). The sample consists of two classes: the experimental class used the educational game "Besaku", while the control class used conventional methods. The instruments used were pretest and posttest questions, student activity observation sheets, and student response questionnaires. The independent sample t-test results showed a significance value of 0.000 < 0.05, indicating that H0 is rejected and Ha is accepted. This means there is a significant effect of using educational games on students' understanding of science concepts. Observations showed students were more active during the learning process, and the questionnaire revealed positive responses to the use of game-based media. The interactive learning flow in the "Besaku" game, which includes material presentation, simulations, quizzes, and digital rewards, proved to support meaningful conceptual understanding.